Faktor - faktor Yang Mempengaruhi Keputusan Konsumen Menggunakan Listrik Prabayar - Wajong, Pamela Christine (JURNAL RISET BISNIS DAN MANAJEMEN, 2019)
This study aims to determine the effect of simultaneous and partial marketing service mix, service quality, and consumer behaviour on consumer decisions using prepaid electricity at PT. PLN (Persero) in Manado City. This study found, both simultaneously and partially the marketing mix, service quality, and consumer behaviour influence consumer decisions. So that it is suggested that the quality of service must be paid more attention by the company through the five indicators and further research needs to examine other factors that might be related to consumer decisions but these variables were not examined in this studyKeywords: Consumer Decision, Service Marketing Mix, Service Quality,Â Â